Experimental study of the flow around two finite square cylinders - Sohankar, A.; Abbasi, M.; Nili-Ahmadabadi, M.; Mahbud Alam, MD.; Zafar, F. (Archives of Mechanics, 2018)
An experimental investigation is conducted on the air flow past two wallmounted finite length side-by-side square cylinders, each of the aspect ratio AR = 7. The cylinder center-to-center spacing ratio T/d is varied from 2 to 6, where d is the side-width of the cylinder. The cylinders are placed at three incidence angles with respect to the freestream velocity, i.e. both cylinders at zero incidence angle (case I), both cylinders at 45° incidence angle (case II), and one cylinder at zero incidence angle with the other at 45° incidence angle (case III). The pressure distributions on the surfaces of the cylinders are measured at Reynolds numbers of 5.9 × 104–8.1 × 104. In addition, the flow structures are visualized in a smoke wind tunnel at the Reynolds number of 2 × 103. Depending on the flow characteristics, four flow structures are identified at the mid-height of the cylinders, namely the asymmetric flow, antiphase shedding flow, leading-edge separated flow and wedge flow. The sectional drag near the bottom is more sensitive to T/d than that near the top. The sectional drag coefficient measured at 0.5d below the mid-span can represent the surface-averaged drag coefficient on the entire cylinder.